Nature of differential sympathetic discharges in chemoreceptor reflexes - Kollai, Mark (1978)
In a study of autonomic reflexes it was found that some produce a generalized, bilaterally uniform response whereas others have an asymmetric or laterality of action. Recordings from vertebral nerve fibers (mainly vasoconstrictors to forelimb muscles), right and left cardiac sympathetics, and renal nerves show that baroreceptors evoke a bilaterally uniform inhibition but chemoreceptors of the carotid sinus and aortic arch initiate a differential discharge. In the chemoreceptor reflex the vagi are activated and bradycardia generally occurs. Vertebral and renal sympathetic fibers increase their activity bilaterally commensurate with the increase in arterial pressure. Sympathetic discharges to the heart, however, are not uniform; they show ipsilateral inhibition and a strong contralateral increase in activity. Stabilization of blood pressure or inactivation of baroreceptors abolishes the ipsilateral inhibition. In isolation, therefore, the chemoreceptor-induced cardiac sympathetic discharge is just quantitatively stronger contralaterally. In the absence of vagi, heart rate changes differ depending on which chemoreceptors are stimulated, because the pacemaker is on the right. Asymmetrical discharges do occur and, in the eventual response to stimulation of chemoreceptors, reflex interactions actually augment the laterality of effects. Peripheral interactions, in the sense that changes effected by one may induce another reflex, are responsible in part for the balances of autonomic activity ultimately seen as the body reacts to stimuli.